Bootstrap site blueprints : design mobile-first responsive websites with Bootstrap 3 - Cochran, David (Community experience distilled., 2014)
A hands-on guide with projects based on fictitious, but common, application development briefs, which will illustrate practical ways of applying responsive web design with Bootstrap. Whether you are a beginner or intermediate web developer, if you wish to make the most of Bootstrap, then this book is for you. You should be familiar with the fundamentals of HTML and CSS, and have some experience incorporating JavaScript plugins. Prior Bootstrap experience is optional.